ANALYSIS OF COMPUTER-BASED MANAGEMENT INFORMATION SYSTEMS AND FINGER PRINT PRESENCE SYSTEMS ON EMPLOYEE PERFORMANCE AT KUALANAMU INTERNATIONAL AIRPORT - Kiki Farida Ferine (Universitas Kristen Indonesia Toraja, 2022)
This study aims to analyze the influence of information-based management systems computers and finger print presence systems on employee performance at Kualanamu International Airport. The study was conducted on 130 employees using the Structural Equation analysis tool.Modeling (SEM) with the help of AMOS version 20.0. The results showed that the management information system and the finger print presence system had a positive and significant effect on employee performance Kualanamu International Airport.